The Effect of Repeated Microwaving Disinfection on the Dimensional Stability of Acrylic Dentures - Nick Polychronakis; Stavros Yannikakis; Alcibiades Zissis (University of Zagreb. School of Dental Medicine, 2014)
Objective. The aim of this study was to evaluate the effect of repeated microwave disinfections on the dimensional stability of acrylic dentures. Materials and Methods. Three groups of dentures made of a heat polymerized acrylic resin were tested. I: dentures kept in water (control group). II: dentures microwaved daily while being immersed into water (wet disinfection). III: dentures microwaved daily without being immersed into water (dry disinfection). Measurements were taken across three reference points, on two occasions: after curing and immersion in water for 24 hours, and one week later. Data obtained were analyzed using one-way analysis of variance (ANOVA) and Scheffe's multiple range test. Results.The results showed that the microwave disinfection provokes dimensional changes of the same pattern (shrinkage). The dentures which underwent wet disinfection exhibited the greatest shrinkage (p<0.05). Conclusions. Disinfection using microwave energy may cause dimensional changes (shrinkage) of complete dentures. The microwave "dry disinfection" method can be safely applied in everyday practice since the dimensional changes which occurred seem to be of no clinical significance.